A comparative study between freeze-dried and spray-dried goat milk on lipid profiling and digestibility - Zhang, Yan; Zheng, Zhaojun; Liu, Chunhuan; Tan, Chin Ping; Xie, Kui; Liu, Yuanfa (Elsevier, 2022)
Different drying techniques impart distinguishing characteristics to goat milk, particularly to its fat globules. Here, we investigated the difference between freeze-dried and spray-dried goat milk (FGM and SGM) fat globules on lipid profiling and in vitro infant gastrointestinal digestibility. The former presented higher levels of MUFA (31.76%) and lower cholesterol content (1.20 ± 0.02 mg/g). Some important long-chain polyunsaturated triacylglycerols such as POL (16:0/18:1/18:2), PSL (16:0/18:0/18:2), and POO (16:0/18:1/18:1), also had better preservation in FGM. Moreover, we detected more species of lysophospholipid in FGM than SGM, accounting for 2.51% and 0.71% of total phospholipids, respectively. More intriguingly, FGM, which has better membrane integrity and larger particle size, showed longer lag during gastric digestion and lower level of final lipolysis throughout gastrointestinal digestion. Therefore, our results showed the effects of different drying techniques on lipid profiling and digestibility of goat milk, providing significant insight for appropriate utilization of goat milk in infant nutrition.